If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) + -1x = -2 + 2x Reorder the terms: 3(-2 + x) + -1x = -2 + 2x (-2 * 3 + x * 3) + -1x = -2 + 2x (-6 + 3x) + -1x = -2 + 2x Combine like terms: 3x + -1x = 2x -6 + 2x = -2 + 2x Add '-2x' to each side of the equation. -6 + 2x + -2x = -2 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + 0 = -2 + 2x + -2x -6 = -2 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 = -2 + 0 -6 = -2 Solving -6 = -2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -2+2x=3(x+3) | | 2j-9=20t | | 9+w=-w-9 | | n^2-n-30= | | -14p+8=22+20p | | (8x+15)=90 | | Y-2.7=22-1 | | 40.55+0.25m=130 | | 3p-4=5p+12 | | (x+3)(x-5)-(4x+2)(x+4)= | | 6sqrt(x-2)-5=4 | | 3x+1=122 | | -2r-1=-8-r | | 4x(5x+4)=155 | | 5v-6/v-12 | | (72y^4)=(9y^7) | | (x^5/6y^3)^-2 | | 1/3x24-6 | | 4X^2=5-9X | | 6(m+2)+14=4+3(m-1) | | 2y+6y+9-5y=24 | | 3e+20=10e+6 | | 90=2(q+25) | | Z=.5a-.5b(6-.2z) | | 3h+1=13 | | 10x-2y=11 | | 2(u-9)-9=-6(-2u+7)-u | | r+10=-9r-10 | | -9y+1=-y+25 | | -5y=-7y-8 | | y-25=9y-1 | | 13z-15z-4=0 |